Log in to add a comment

## Answers

xdy/dx + y = 0

dy/dx = -y/x

dy/dx = -b/a {slope at point (a,b)}

equation of tangent ;

(y-b) = (-b/a)(x-a)

ay - ab = -bx + ab

bx + ay = 2ab or

x/a + y/b = 2

differentiating the above curve at (a,b) we get slope of that tangent at that point

x*dy/dx + y = 0

x*dy/dx = -y

dy/dx= -y/x

slope at the point (a,b)

dy/dx = -b/a

the equation of the tangent at (a,b)

(y-b) = -b/a (x-a)

a(y-b)= -b(x-a)

ay-ab = -bx +ab

bx+ay -2ab = 0

This is equation of tangent at the point (a,b)